ANALISA DESAIN PRODUK BOOKTORY TELLING SEBAGAI PERANGKAT PAMER BUKU AJAR UNGGULAN UNTUK DOSEN UNIPA SURABAYA - Yitno Utomo (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Booktory telling is a product that can be used as a book showing device. This study aims to find out attribute of books that tell about quality homes and provide designs based on respondents satisfaction. The research sample amounted to 86 respondents who were conducted by purposive sampling technique. Data analysis uses Quality Function Deployment (QFD). The results of the analysis result in the importance of 3 Main Priorities namely; The Relatively Important Result (RI) of 25% is prioritized on the design of the red booktory telling product with HPL material. The Relatively Important Results (RI) of 21% are prioritized on strong selected ingredients. The materials selected by the 17% Relative Important Results (RI) were prioritized on the part of the story that briefly told the book and the writer's wealth made from an artpaper screen.